Improvement mechanical and antibacterial properties of epoxy by polyethylene glycol and Ag/CuO nanoparticles. Issue 9 (26th February 2019) - Ashrafi, Mahdi; Hamadanian, Masood; Ghasemi, Ahmad Reza; Kashi, Fereshteh Jookar
Abstract : In this study, effect of the polyethylene glycol (PEG), temperature and time of curing on mechanical properties of epoxy resin were optimized using response surface methodology method. With increasing PEG, elongation increased but yield, ultimate strength, and Young modulus decreased. In the next step Ag/CuO (molar ratio: 1/5) nanoparticles (NPs) were synthesized by ultrasonic route, then was added to optimized epoxy/PEG, which led to significant enhancement of antibacterial activity and mechanical properties of optimized epoxy/PEG. Comparing yield and ultimate strength of the epoxy/PEG/(Ag/CuO) with pure epoxy showed amplification of the 70.17 and 81.41%, respectively. Optimized epoxy/PEG and Ag/CuO NPs were characterized by FT‐IR, XRD, SEM, EDX, TGA, and DRS. POLYM. COMPOS., 40:3393–3401, 2019. © 2019 Society of Plastics Engineers